Treatment of visual axis opacification and secondary membranes with Nd:YAG laser after pediatric cataract surgery under intranasal sedation - Chang, Pingjun; Li, Siyan; Wang, Dandan; Chen, Chaoqiao; Fu, Yana; Hu, Man; Qian, Shuyi; Zhao, Yun-e (Frontiers in Pediatrics, 2023)
Purpose: To describe neodymium-doped yttrium-aluminum-garnet (Nd:YAG) laser treatment of visual axis opacification and secondary membranes in pediatric patients with cataracts under intranasal dexmedetomidine sedation. Methods: Twenty eyes of 17 patients with secondary membrane formation after cataract extraction were enrolled in this study. Intranasal dexmedetomidine sedation (3 ug/kg) was administered, and Nd:YAG laser (Ellex Super Q, Adelaide, Australia) procedures were performed with children in the sitting position with their chin supported on a laser delivery slit lamp. Preoperative and postoperative visual acuities were documented, and medical records were reviewed. Results: The age of the patients ranged from 5 to 83 months (31.82 ± 27.73). Nineteen (95.0%) eyes had congenital cataracts and one (5.0%) had a traumatic cataract. Nd:YAG laser treatment of VAO with ten (50.0%) eyes, pupillary membranes with three (15.0%) eyes, pupillary cortical proliferation with six (30.0%) eyes, and anterior capsule contraction with one (5.0%) eye. Five (25.0%) eyes demonstrated visual acuity improvement, whereas six (30.0%) eyes remained unchanged after laser treatment. The recurrence rate was 30.0% and four eyes underwent a second Nd:YAG membranectomy. No side effects or tolerances due to sedative drugs were observed. Conclusion: Nd:YAG laser membranectomy under intranasal dexmedetomidine sedation was safely performed in children as young as 5 months old in a sitting position. This approach facilitates patient convenience, doctor proficiency, and cost reductions. Patients with recurrence can be treated by repeating the procedure.